Freshwater prawns of the genus Macrobrachium Bate, 1868 (Crustacea, Decapoda, Palaemonidae) from Laos - Hanamura, Yukio; Imai, Hideyuki; Lasasimma, Oulaytham; Souliyamath, Pany; Ito, Sayaka (Zootaxa, 2011)
Caridean prawns of the genus Macrobrachium Bate, 1868 (Crustacea, Decapoda, Palaemonidae) collected from the Laotian river system were studied. Fourteen species are recognised in this study, including one unidentified species. Their taxonomy is discussed and illustrated, of which 11 species are new records to the Laotian fauna. The identity of species of the “M. dienbienphuense” group has been remained obscure, and this study, which incorporated the 16S rRNA mitochondrial gene analysis, demonstrated that M. amplimanus Cai & Dai, 1999, M. dienbienphuense Dang & Nguyen, 1972, and M. eriocheirum Dai, 1984 are valid species. The Macrobrachium fauna in Laos exhibited closer affinity to that of the tropical Indo-China and Sunda elements (southern Yunnan Province, south-western China, northern Vietnam as well as north and north-eastern Thailand), implying that the Mekong River system contributes substantially to the regional freshwater prawn biodiversity.